The Effects of Input and Characteristic Factors on Contact Rate Achievement among Puskesmas in Indonesia - Makarim, Iqbal Andri; Pujiyanto, Pujiyanto (Journal of Indonesian Health Policy and Administration, 2025)
The contact rate is the lowest-performing indicator in the Performance-Based Capitation Payment system initiated by BPJS Kesehatan. Analysis of the 2019 National Health Facility Research (Rifaskes) data showed that less than half of Puskesmas in Indonesia achieved the target. This cross-sectional study analyzed 5,384 Puskesmas from the 2019 Rifaskes to examine the effect of input and characteristic factors on achieving the contact rate. Independent variables included health worker ratios (doctors, nurses, midwives per 5,000 participants), completeness of essential medical equipment, communication facilities, P-Care application use, and Puskesmas characteristics. Multivariate logistic regression identified four significant factors: doctor ratio (OR=1.06; p<0.0001), midwife ratio (OR=1.01; p=0.033), completeness of essential medical equipment (OR=1.16; p=0.029), and BLUD-based financial management (OR=1.13; p=0.029). These factors explained only 2.6% of the variance (Nagelkerke R²=0.026), suggesting other unmeasured influences. Policy implications include equitable distribution of health personnel, targeted procurement of essential equipment, strengthening financial autonomy through BLUD, and optimizing P-Care data utilization to improve service accessibility and performance.